Global experiences in water reuse: summary and recommendations for the USEPA 2012 water reuse guidelines - Silva, A. da; Drechsel, Pay; Keraita, Bernard N.; Lautze, Jonathan F.; Stander, E. (2011)
The international chapter of the 2012 EPA Water Reuse Guidelines is currently under development. This chapter aims to identify tools and approaches used in the international context that can strengthen water reuse in the US. The main objective is to review international experiences in order to gain insights on existing and best practices for governments, international development agencies, practitioners, and development partners interested in the challenges and opportunities within water reuse. Unlike earlier versions, the updated chapter aims to more fully discuss the full spectrum of applications in a range of resource contexts and highlight successes, challenges, and lessons learned in practical applications across a range of resource settings through a collection of case studies. The focus is on local and regional best practices and considerations for ensuring that water reuse occurs in a safe and sustainable manner. This applies to planned reuse schemes, with an emphasis on engineering practices for wastewater treatment, as well as unplanned systems, with an exploration of so-called post- or non-treatment options for reducing health risks. Factors that enable safe and sustainable reuse for both planned schemes and unplanned systems, such as institutional strengthening, financial planning, stakeholder processes, and public acceptance campaigns, will be discussed along with a framework for transitioning from unplanned to planned reuse.